1992
DOI: 10.1037/0022-3514.63.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Once a boring task always a boring task? Interest as a self-regulatory mechanism.

Abstract: A process was proposed through which individuals regulate their motivation to perform necessary but uninteresting activities over time. If committed to continuing, individuals may engage in interest-enhancing strategies that can change the activity into something more positive to perform. In Study 1 Ss performed novel tasks and generated strategies to make regular performance interesting. In Study 2 Ss actually used these strategies primarily in conditions indicating a self-regulatory attempt: The task was cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
287
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 324 publications
(303 citation statements)
references
References 37 publications
7
287
1
8
Order By: Relevance
“…Previous work by Sansone and colleagues has suggested that when faced with an uninteresting but important activity, individuals may strategically engage in actions that make performance more interesting, thereby enhancing motivation to persist (Sansone & Smith, 2000;Sansone, Weir, Harpster, & Morgan, 1992). However, these actions may also hinder performance, at least in the short term (Sansone & Thoman, 2005).…”
Section: Studymentioning
confidence: 97%
See 3 more Smart Citations
“…Previous work by Sansone and colleagues has suggested that when faced with an uninteresting but important activity, individuals may strategically engage in actions that make performance more interesting, thereby enhancing motivation to persist (Sansone & Smith, 2000;Sansone, Weir, Harpster, & Morgan, 1992). However, these actions may also hinder performance, at least in the short term (Sansone & Thoman, 2005).…”
Section: Studymentioning
confidence: 97%
“…This relationship over time may be particularly important when one examines the possibility of self-regulation of motivation. Sansone and colleagues have noted the potential trade-offs between doing something to make a currently boring but important task more interesting and indices of performance (Sansone et al, 1992;. In particular, if the strategies that might make a task more interesting take time, attention, or effort away from the things that maximize performance, then performance may be hurt.…”
Section: Performance and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sansone, Weir, Harpster, & Morgan (1992) suggest that strategies that regulate interest can help people maintain their motivation to perform the task. Individuals often attempt to regulate their motivation for important activities by using the social context of the activity to make their experience more interesting.…”
Section: Discussionmentioning
confidence: 99%